Charting the COVID-19 vaccination journey in Saudi Arabia: Insights into post-vaccination adverse effects and immunization dynamics - Subaiea, Gehad M.; Alkhateeb, Nawaf; Sahman, Faisal; Alsudayri, Abdulrahman; Almudayni, Abdulkarim M.; Alrashidi, Hamoud; Alshammari, Abdulrahman M; Alamri, Abdulwahab; Almuntashiri, Sultan; Hussain, Arshad; Khloofi, Heba Ali; Anwar, Sirajudheen (Frontiers in Pharmacology, 2025)
BackgroundThe current study evaluated the effects of different COVID-19 vaccines on Saudi Arabian residents, focusing on their safety, acceptance, and effectiveness. Gaining a better knowledge of these vaccination results will help develop more successful public health initiatives and increase confidence in vaccination campaigns throughout the Kingdom.MethodsA cross-sectional study was conducted with 401 participants from diverse backgrounds, covering different ages, genders, nationalities, weights, and education levels. The survey gathered information about participants’ health conditions, their vaccines, side effects, and infection rates before and after vaccination. The data were analyzed to compare vaccine preferences, side effects, and infection trends overtime.ResultsSociodemographic-wise, most participants were men (62.84%) and Saudi nationals (96.01%), showing significant differences by gender and nationality (P < 0.001). The largest age group was 21–30 years (45.89%, P < 0.001), with 66.58% being university graduates (P < 0.001). Pfizer/BioNTech was the top choice across all doses, with 83.46% receiving it for the first dose, 78.1% for the second, and 39.28% for the third, reflecting a clear preference over other vaccines (P < 0.001). Pfizer/BioNTech recipients reported side effects after the first dose in 36.53% of cases, but only 1.86% needed medical help. Vaccination significantly reduced infection rates: Pfizer/BioNTech dropped infection rates from 43.18% to 8.33% after the third dose (P < 0.001), while Oxford/AstraZeneca saw rates fall from 12.88% to 0.76% after the third dose, but did not reach significance (P = 0.34). Overall, vaccinated individuals had much lower infection rates (28.17%) than among unvaccinated ones (100%), with a P-value of 0.020.ConclusionOur results concluded that Saudi Arabia’s vaccination campaign has proven effective, especially after the second and third doses. Pfizer/BioNTech was the most preferred vaccine, demonstrating strong efficacy and safety, which helped build public confidence. Ongoing monitoring is crucial to maintaining pandemic control, post-marketing and public health strategies.